BIOLARVACIDE ACTIVITY OF ETHANOL EXTRACT OF KEDONDONG STEM (Spondias pinnata) AGAINST Aedes aegypti - Moniharapon, Debby D; Ukratalo, Abdul Mahid; Wisnanda, Bayu (RUMPHIUS, 2019)
Aedes aegypti mosquito is a vector for Dengue Hemorrhagic Fever. One effort to prevent the spread of the disease is vector control. The use of insecticides is a form of vector control in an effort to control DHF. There are two broad categories of insecticides that are often used as household insecticides, namely insecticides that function to kill insects and insecticides that function to repel insects. Kedondong (Spondias pinnata) which is a family of anacardiaceae which generally grows well in tropical climates. Kedondong bark contains saponins, alkaloids, and flavonoids which are secondary metabolites involved in defense mechanisms against attack by many microorganisms. This study aims to determine the biolarvicidal activity of the ethanol extract of kedondong stem bark in killing Aedes aegypti mosquito larvae. This study used 5 treatments and 3 replications. Each treatment contained 20 Aedes aegypti mosquito larvae. Observations were made for 24 hours with observation times of 0 hours, 6 hours, 12 hours, 18 hours and 24 hours. The time calculation starts after the larvae are inserted into the experimental bottle. The results showed that kedondong bark extract was able to kill Aedes aegypti mosquito larvae. The effective dose of ethanol extract of kedondong stem bark in killing Aedes aegypti mosquito larvae is 20 mg/mL.